2010
DOI: 10.1097/ico.0b013e3181bd9f79
|View full text |Cite
|
Sign up to set email alerts
|

Time-Kill Assay Results for a Linalool-Hinokitiol-Based Eyelid Cleanser for Lid Hygiene

Abstract: This linalool-hinokitiol-based eyelid cleanser may be helpful in the outpatient setting for patients with presurgical, blepharitis, punctal plug and dry eye, and in the inpatient setting for patients who are allergic to iodine, or as an adjunct to povidone-iodine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…The broad anti-bacterial activity of β-thujaplicin (Hinokitiol, 47 ) and γ-thujaplicin ( 48 ) was reported several decades ago. 8 , 28 , 29 Our results revealed modest inhibition of both Gram-positive bacteria ( S. aureus ) and Gram-negative rods ( E. coli and A. banmannii ), which is consistent with previous reports ( Table S1 ). Two α-HT, 261 and 262 , also showed broad inhibition against both Gram-positive and Gram-negative bacteria ( Table 2 ).…”
Section: Discussionsupporting
confidence: 93%
“…The broad anti-bacterial activity of β-thujaplicin (Hinokitiol, 47 ) and γ-thujaplicin ( 48 ) was reported several decades ago. 8 , 28 , 29 Our results revealed modest inhibition of both Gram-positive bacteria ( S. aureus ) and Gram-negative rods ( E. coli and A. banmannii ), which is consistent with previous reports ( Table S1 ). Two α-HT, 261 and 262 , also showed broad inhibition against both Gram-positive and Gram-negative bacteria ( Table 2 ).…”
Section: Discussionsupporting
confidence: 93%
“…Recently, time-kill results for a linalool-hinokitiolbased eyelid skin cleanser proved superior to povidone-iodine 10% against S aureus and MRSA. 64 While bacteria may gain intraocular access during surgery, 65,66 it has been demonstrated that povidone-iodine conjunctival irrigation effectively prevents intracameral contamination during phacoemulsification. 67 An evidence-based assessment of endophthalmitis prophylaxis found that preoperative povidone-iodine antisepsis received the highest rating and was the only measure that gained a "B" grade (meaning moderately important to clinical outcome).…”
Section: Operative Site Antisepsismentioning
confidence: 99%
“…This major bioactive compound is used in certain health care products, such as safe preservatives for toothpaste, cosmetics, hair tonics, mouth care gel, eyelid cleanser, hair restorers, skin lotions, and body soap, because of its multiple biological activities (Gilbard et al, 2010;Nagao and Sata, 2011). Hinokitiol has also been reported to regulate immune cell function by inhibiting the production of tumor necrosis factor-α from lipopolysaccharide-stimulated macrophages through the inhibition of NF-κB activity (Byeon et al, 2008).…”
Section: Introductionmentioning
confidence: 98%